The role of gemini surfactant and SiO2/SnO/Ni2O3 nanoparticles as flow improver of Malaysian crude oil - VijayaKumar, Shamala Devi; Junaidi, Zakaria; Norida, Ridzuan (Elsevier B.V., 2021)
The addition of surfactants and nanoparticles in minimizing wax deposition related problems such as flow assurance is considered an attractive alternative among other techniques but limited researches have been carried out in investigating the method. High viscosity crude oil needs to be treated with viscosity reducer to facilitate transportation and processing. In this study, the efficiency of the viscosity reducer, a Gemini surfactant 2,5,8,11 Tetramethyl 6 dodecyn-5,8 Diol Ethoxylate, three different nanoparticles: silicon dioxide (SiO2), tin oxide (SnO) and nickel (III) oxide (Ni2O3) and their novel blends at different range of concentration, temperature, shear rate and surfactant/nanoparticle loading ratio are assessed in order to study their influence on the viscosity of Malaysian crude oil using Brookfield DV-III viscometer. The separate use of Gemini surfactant and nanoparticles alone resulted in significant reduction in crude oil viscosity. The combined use of Gemini surfactant and nanoparticles showed better performance as compared to their corresponding individual use. The presence of surfactant improves the adsorption of nanoparticles by functionalizing their surfaces. Adsorption and adhesion of wax molecules onto the surface of nanoparticles and surfactants prevents them from aggregating. This results in increment in viscosity reduction. Overall, the viscosity of crude oil was reduced about 85–92% at 10 ℃ with the aid of Gemini surfactant and nanoparticles. The highest viscosity reduction obtained was 92.8% using the blend of Gemini surfactant and silicon dioxide. The findings of the study are expected to contribute to the crude oil industry in improving flow in production and transportation.